The State of Neurocritical Care Fellowship Training and Attitudes toward Accreditation and Certification: A Survey of Neurocritical Care Fellowship Program Directors - Dhar, Rajat; Rajajee, Venkatakrishna; Finley Caulfield, Anna; Maas, Matthew B.; James, Michael L.; Kumar, Avinash Bhargava; Figueroa, Stephen A.; McDonagh, David; Ardelt, Agnieszka (Frontiers in Neurology, 2017)
Neurocritical care as a recognized and distinct subspecialty of critical care has grown remarkably since its inception in the 1980s. As of 2016, there were 61 fellowship training programs accredited by the United Council for Neurologic Specialties (UCNS) in the United States and more than 1,000 UCNS-certified neurointensivists from diverse medical backgrounds. In late 2015, the Program Accreditation, Physician Certification, and Fellowship Training (PACT) Committee of the Neurocritical Care Society (NCS) was convened to promote and support excellence in the training and certification of neurointensivists. One of the first tasks of the committee was to survey neurocritical care fellowship training program directors to ascertain the current state of fellowship training and attitudes regarding transition to Accreditation Council for Graduate Medical Education (ACGME) accreditation of training programs and American Board of Medical Specialties (ABMS) certification of physicians. First, the survey revealed significant heterogeneities in the manner of neurocritical care training and a lack of consistency in requirements for fellow procedural competency. Second, although a majority of the 33 respondents indicated that a move toward ACGME accreditation /ABMS certification would facilitate further growth and mainstreaming of training in neurocritical care, many programs do not currently meet administrative requirements and do not receive the level of institutional support that would be needed for such a transition. In summary, the results revealed that there is an opportunity for future harmonization of training standards and that a transition to ACGME accreditation /ABMS certification is preferred. While the results reflect the opinions of more than half of the survey respondents, they only represent a small sample of neurointensivists.